2004
DOI: 10.1111/j.1348-0421.2004.tb03475.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Monoclonal Antibody, Specific for Intracellular Orientia tsutsugamushi, to Immunofluorescent Antibody Test for Determining Antibiotic Susceptibility

Abstract: Abstract:The simple quantification of viable intracellular bacteria is important for the study of an obligate intracellular bacterium, Orientia tsutsugamushi. We applied a novel monoclonal antibody (M686-13) -specific for intracellular Orientia-to an immunofluorescent antibody (IFA) test for determining antibiotic susceptibility of O. tsutsugamushi. M686-13 did not react with Orientia that was inhibited by doxycycline, although bacterial particles still remained in the cells. This preferential staining of prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This result is consistent with that of our previous study, in which we determined the antibiotic susceptibility of both strains using IFA (7). However, strain AFSC-4 is reported to be doxycycline-resistant and its MIC was reported to be 0.25 µg/mL (5).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with that of our previous study, in which we determined the antibiotic susceptibility of both strains using IFA (7). However, strain AFSC-4 is reported to be doxycycline-resistant and its MIC was reported to be 0.25 µg/mL (5).…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study, we reported the characteristics of a monoclonal antibody (MAb), M686-13, that reacts exclusively with intracellular O. tsutsugamushi , and its application in an immunofluorescence assay (IFA) to determine antibiotic susceptibility (6, 7). However, that method requires the manual count of bacterial particles or computer-assisted scanning.…”
Section: Introductionmentioning
confidence: 99%
“…in insect cells (22). Thus, this strikingly low MIC of CorA was specific for O. tsutsugamushi, and it is lower than the MICs observed for any other antimicrobial substance that has been so far tested against O. tsutsugamushi (32)(33)(34)(35)(36). A possible exception may be the tetracycline derivative tigecycline, which was recently shown to inhibit growth in vitro of O. tsutsugamushi (37), but which awaits susceptibility testing in vivo.…”
Section: Discussionmentioning
confidence: 93%